Quantitative evaluation of enterprise marketing activities - Ginevičius, Romualdas; Podvezko, Valentinas; Ginevičius, Adomas (Journal of Business Economics and Management, 2013)
The growing competition on the international markets means that the importance of enterprise marketing activities is increasing. However, the attention paid to theoretical and practical marketing problems by enterprises is insufficient. This particularly refers to the analysis of marketing strategy effectiveness. It is not clear how marketing affects enterprise performance. To perform this analysis, the quantitative evaluation of enterprise marketing activities is required. Enterprise marketing is a complex multi-faceted phenomenon. Its various aspects are described by multidimensional and often oppositely directed criteria. Therefore, in this case, multicriteria evaluation methods can be successfully used for analysis. The state of the enterprise marketing system is described by sets of criteria. Therefore, the problem of adequate evaluation of their weights arises. Sometimes, it is possible to reduce the number of evaluation criteria by developing their hierarchical system. However, the question arises how the transformation of a single-level system of criteria into the respective multi-level system affects the calculation results.